2002
DOI: 10.1002/jsfa.1260
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of the small intestine of the calf: effect of dietary protein source on the activities of some enzymes in the small intestinal mucosa and digesta

Abstract: The objective of this study was to examine the effect of dietary protein source on the morphology and enzyme activities in the small intestinal mucosa and digesta of preruminant calves. The control diet contained skim milk powder. Plant proteins from soy concentrate (unhydrolysed or partially hydrolysed) and potato concentrate were incorporated into experimental diets. Duodenal, jejunal and ileal mucosal biopsies and digesta were collected from calves fitted with simple cannulae and continuously infused with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…At the duodenum, fraction M r > 20,000 probably contained endogenous proteins from digestive secretions, including enzymes and mucus, and proteins sloughedoff in the lumen from the lining of anterior segments of the gut, as suggested by Montagne et al (2000) and Montagne et al (2002). Endogenous proteins flowing at the duodenum are hydrolyzed and absorbed proximodistally by the same mechanisms as dietary proteins.…”
Section: Effect Of Dietary Cp Level On Digestion Of Cp Along the Smalmentioning
confidence: 82%
“…At the duodenum, fraction M r > 20,000 probably contained endogenous proteins from digestive secretions, including enzymes and mucus, and proteins sloughedoff in the lumen from the lining of anterior segments of the gut, as suggested by Montagne et al (2000) and Montagne et al (2002). Endogenous proteins flowing at the duodenum are hydrolyzed and absorbed proximodistally by the same mechanisms as dietary proteins.…”
Section: Effect Of Dietary Cp Level On Digestion Of Cp Along the Smalmentioning
confidence: 82%
“…The specific activity of aminopeptidase N (EC 3.4.11.2) was determined according to Sangild et al (1995). The specific activity of alkaline phosphatase (EC 3.1.3.1) was determined according to Martins et al (2000) Alkaline phosphatase and aminopeptidase N were retained because the former is considered to be a biomarker of intestinal maturation and the latter, which contributes to peptide digestion, was found to vary similarly to other peptidases (aminopeptidase A and dipeptidylpeptidase IV) in piglets and calves fed various legume protein sources (Salgado et al 2001;Montagne et al 2002). Protein was measured by the method of Lowry et al (1951) and specific enzyme activities were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance is that Montagne et al ( 60 ) reported that the partial substitution of soya protein concentrate for skimmed milk powder increased alkaline phosphatase activity in the duodenum and jejunum by approximately 33%, which was more pronounced with soya protein isolate. Phytate was probably present in both soya preparations ( 57 ) and may have triggered these increases in alkaline phosphatase activity.…”
Section: Protein–phytate Interactionsmentioning
confidence: 99%